2023
DOI: 10.3390/ijms241210137
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Screening for Miscarriage or Stillbirth—Prediction Model Based on MicroRNA Biomarkers

Abstract: We evaluated the potential of cardiovascular-disease-associated microRNAs to predict in the early stages of gestation (from 10 to 13 gestational weeks) the occurrence of a miscarriage or stillbirth. The gene expressions of 29 microRNAs were studied retrospectively in peripheral venous blood samples derived from singleton Caucasian pregnancies diagnosed with miscarriage (n = 77 cases; early onset, n = 43 cases; late onset, n = 34 cases) or stillbirth (n = 24 cases; early onset, n = 13 cases; late onset, n = 8 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Cui et al reported an overexpression of serum miRNA-371a-5p and down expression of miRNA-206 [40]. Recently, Hromadnikova et al proposed a predictive model for miscarriage based on the blood expression of eight miRNAs (upregulation of miRNA-1-3p, miRNA-16-5p, miRNA-17-5p, miRNA-26a-5p, miRNA-146a-5p, and miRNA-181a-5p and downregulation of miRNA-130b-3p and miRNA-195-5p) identifying patients at risk in 80.52% of cases [41]. All the above studies are summarized in Table 1.…”
Section: Pathologies Associated With Pregnancy 41 Early and Late Misc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al reported an overexpression of serum miRNA-371a-5p and down expression of miRNA-206 [40]. Recently, Hromadnikova et al proposed a predictive model for miscarriage based on the blood expression of eight miRNAs (upregulation of miRNA-1-3p, miRNA-16-5p, miRNA-17-5p, miRNA-26a-5p, miRNA-146a-5p, and miRNA-181a-5p and downregulation of miRNA-130b-3p and miRNA-195-5p) identifying patients at risk in 80.52% of cases [41]. All the above studies are summarized in Table 1.…”
Section: Pathologies Associated With Pregnancy 41 Early and Late Misc...mentioning
confidence: 99%
“…SerumHromadnikova et al[41] 2023 181 Upregulated: miRNA-1-3p, miRNA-16-5p, miRNA-17-5p, miRNA-26a-5p, miRNA-146a-5p, miRNA-181a-5p Downregulated: miRNA-130b-3p, miRNA-195-5p…”
mentioning
confidence: 99%
“…Since increased levels of miR-146a, miR-155 and miR-210 have been found in placentas of aPLnegative RPL [134,[158][159][160] and PE patients [135][136][137]139,[161][162][163] it could be concluded that aPL-induced upregulation of named miRNAs in trophoblast cells is a contributing factor to the development of these obstetric complications in OAPS patients. Moreover, increased levels of miR-146a, miR-155 and miR-210 were found in blood of patients suffering from pregnancy loss and/or PE [140,[164][165][166][167] suggesting the use of these miRNAs as biomarkers for early diagnostics as well as mechanism-based targets of new therapeutics for RPL and PE associated or not with OAPS.…”
Section: Non-coding Rnas-emerging Players In Oaps Pathophysiologymentioning
confidence: 99%
“…Our research group [ 7 ] also introduces a first-trimester predictive model for late miscarriage and stillbirth based on the altered expression of microRNA biomarkers in maternal whole peripheral blood and selected maternal clinical characteristics that represent risk factors for miscarriage and stillbirth.…”
mentioning
confidence: 99%